Biomechanical analysis of conventional and sumo deadlift - Hanen, N. C.; Ben Mansour, K.; Ertel, G. N.; Duchene, Y.; Gauchard, G. C. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe conventional (CDL) and sumo (SDL) deadlifts are two fundamental techniques used in competitive lifting and as effective exercises for strengthening the knee and hip muscles. This study aims to investigate their biomechanical differences through a comprehensive analysis of joint kinematics, joint kinetics, and muscle activation.Materials and MethodsThirty experienced male lifters performed both CDL and SDL at 85% of their one repetition maximum (1-RM). Lower limb joint range of motion (ROM), internal joint moments, and muscle activation of key lower limb and spinal muscles were recorded and analyzed. Paired t-tests and Statistical parametric mapping (SPM) were used to compare parameters between lifting techniques (p < 0.025).ResultsSDL showed greater ROM in the frontal and transverse planes, particularly at the hip and knee, whereas CDL involved greater hip flexion and ankle dorsiflexion. CDL generated higher hip extension moments, while SDL produced greater frontal and transverse plane joint moments at the hip and knee. Additionally, SDL induced a greater ankle inversion moment. In the transverse plane, ankle moments were higher in CDL during phase 1 and became greater in SDL in phase 2. Regarding EMG peak values, the biceps femoris exhibited greater activation in CDL across both phases. The tibialis anterior and the erector spinae thoracis demonstrated greater activation in CDL during phase 1 and phase 2, respectively. Conversely, the vastus lateralis exhibited higher peak activation in SDL, but only during phase 1.ConclusionCDL is more effective for targeting posterior chain, particularly the hip extensors, while SDL emphasizes anterior chain involvement and induces greater mediolateral stabilization demands. SDL may be particularly beneficial for knee reinforcement and increases frontal plane demands, supporting its relevance in rehabilitation contexts that require enhanced mediolateral stability. These findings highlight the importance of selecting the appropriate deadlift technique according to specific training or rehabilitation objectives.